O papel formativo das línguas estrangeiras no Brasil - Pacanco, Deise (Diálogos Latinoamericanos, 2009)
This article focuses on linguistic education and language teaching in Brazil in the last decades. Firstly, it approaches the fact that some data about Brazilian population and linguistic education can throw light on some aspects of the topic in question. Afterwards, the article relates such data to theoretical and methodological issues, as they appear in documents and curriculum standards from recent years. In order to do this, the discussion is based on authors from the French Discourse Analysis School and the Bakhtin Circle. Finally, the article points to the formative role of foreign language in the context of basic education and human formation in general, through the notions of intersubjectivity and interculturality.